Comparative Analysis of Sorrow in Shakespeare’s Juliet and Homer’s Andromache - Chakraborty, Sanjukta; Gulati, Varun; Sharma, Deepali (Literatūra, 2025)
The most memorable protagonists in any given piece of Classical Literature are often the characters who face and overcome the greatest psychological trials and obstacles. This article studies the choices of two such characters who both experience extreme and unimaginable sorrow – Homer’s Andromache and Shakespeare’s Juliet. While one character is content with her role in society, the other tries to break convention in order to be with her love. A deeper psychoanalytical study of their actions and choices, with particular emphasis on the effects of ‘sorrow’ through the lens of Freud’s concepts of bereavement and melancholia, are analyzed in this article. From love and contentment, both women face trials and tribulations which lead to loss and death. However, both these characters’ reactions toward their sorrows are what set them apart from one another; while one woman is idolized as the quintessential pinnacle of womanhood for all generations, the other is immortalized as the rebellious protagonist of a Shakespearean Romantic tragedy.